2023
DOI: 10.3390/ijms241511900
|View full text |Cite
|
Sign up to set email alerts
|

Alternations of NF-κB Signaling by Natural Compounds in Muscle-Derived Cancers

Abstract: The NF-κB-signaling pathway plays a crucial role in cancer progression, including muscle-derived cancers such as rhabdomyosarcoma or sarcoma. Several natural compounds have been studied for their ability to alter NF-κB signaling in these types of cancers. This review paper summarizes the current knowledge on the effects of natural compounds, including curcumin, resveratrol, quercetin, epigallocatechin-3-gallate, and berberine, on NF-κB signaling in muscle-derived cancers. These compounds have been shown to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…This process further accelerates the transcription of various proinflammatory cytokines, proteinases, and prostaglandins, contributing to the activation of inflammatory cells (macrophages and neutrophils) ( 45 ). On the other hand, the alternative signaling pathway of NF-κB is primarily involved in lymphoid organogenesis and the activation of the adaptive immune response ( 46 ). In contrast to the canonical NF-κB signaling pathway, the alternative signaling pathway is activated by a subset of Tumor Necrosis Factor Receptor (TNFR) superfamily members, including CD40, the lymphotoxin-β receptor (LTβR), receptor activator of NF-κB ligand (RANK), and B lymphocyte stimulating factor receptor (BAFFR) ( 47 ).…”
Section: Nf-κb “Identity Card”mentioning
confidence: 99%
“…This process further accelerates the transcription of various proinflammatory cytokines, proteinases, and prostaglandins, contributing to the activation of inflammatory cells (macrophages and neutrophils) ( 45 ). On the other hand, the alternative signaling pathway of NF-κB is primarily involved in lymphoid organogenesis and the activation of the adaptive immune response ( 46 ). In contrast to the canonical NF-κB signaling pathway, the alternative signaling pathway is activated by a subset of Tumor Necrosis Factor Receptor (TNFR) superfamily members, including CD40, the lymphotoxin-β receptor (LTβR), receptor activator of NF-κB ligand (RANK), and B lymphocyte stimulating factor receptor (BAFFR) ( 47 ).…”
Section: Nf-κb “Identity Card”mentioning
confidence: 99%
“…As different studies have shown, NF-κB modulates a plethora of cellular processes, including cell proliferation, angiogenesis, and apoptosis suppression, making it an important link in promoting inflammation, cancer proliferation, and drug resistance [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. NF-κB is activated in an inflammatory milieu and regulates various pro-inflammatory cytokines (TNFα, IL-6, IL-1β) as well as STAT3, a transcription factor that activates proliferative and survival genes in cancer cells [ 10 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, while apoptosis activation is always desired in cancer treatment, autophagy has a much more complex role and can induce tumor suppression or tumor proliferation, depending on the tumor stage [ 25 , 26 , 27 , 28 ]. Due to increasing multidrug resistance in cancer, numerous studies are now using natural products to target NF-κB and induce apoptosis or autophagy, leading to cancer suppression [ 3 , 16 , 29 , 30 , 31 , 32 , 33 ]. Furthermore, many of these phytochemicals, such as curcumin, resveratrol, and lycopene, exert their anti-cancer activity not only by targeting NF-κB but also by controlling epigenetic modifications, which are key regulators of apoptosis and autophagy [ 30 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation